Ypotramaé: uma compreensão junguiana da iniciação do pajé - Oliveira, Luciano Diniz de (2012)
The aim of the present work is to understand the psychological process underlying the initiation of the pajé . This aim was pursued using Analytical Psychology as a theoretical background. The pajé is a figure of central importance within Indian societies and the process of his initiation is looked upon as an important phenomenon as regards Analytical Psychology, because it constitutes a process of conscience transformation. In order to achieve a better understanding of this issue aspects of native cultures as initiation rites and shamanism were analyzed on the basis of Analytical Psychology. An interview of a Kamaiurá pajé , enriched with Analytical Psychology concepts was also utilized